2023
DOI: 10.1038/s41598-023-31477-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality-based intervention on depression in stroke patients: a meta-analysis

Abstract: As one of the most common neuropsychiatric complications after stroke, post-stroke depression can significantly affect the initiative of rehabilitation exercise and the rehabilitation of neurological function of patients. Virtual reality (VR) has been widely used in health-related fields in recent years. There is some evidence that VR-based interventions have benefits for depression. The aim of this study was to assess the effectiveness of VR-based intervention on depression in stroke patients. A total of 752 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Additionally, the study by Onieva et al, 2018 [45] reported improvements in depressive symptoms in patients with mild Alzheimer's disease. In line with our scores, other studies have confirmed an improvement in depression in patients with head trauma [31] and stroke [35] through virtual reality compared to conventional therapy. Neuropsychological research in depression therapy confirms the therapeutic value of digital interventions, highlighting the release of hormones such as endorphins and striatal dopamine, responsible for feelings of pleasure and well-being, during the patient's interactive experiences with virtual reality [34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the study by Onieva et al, 2018 [45] reported improvements in depressive symptoms in patients with mild Alzheimer's disease. In line with our scores, other studies have confirmed an improvement in depression in patients with head trauma [31] and stroke [35] through virtual reality compared to conventional therapy. Neuropsychological research in depression therapy confirms the therapeutic value of digital interventions, highlighting the release of hormones such as endorphins and striatal dopamine, responsible for feelings of pleasure and well-being, during the patient's interactive experiences with virtual reality [34].…”
Section: Discussionsupporting
confidence: 91%
“…No studies have been found in the literature investigating VR-ROT in patients with severe acquired brain injury by obtaining a single cognitive functioning score, but it is examined in a fragmented manner, not allowing a comprehensive and integrated view regarding the time, place, and orientation of the person. Furthermore, neuropsychological research in the treatment of depression demonstrates the therapeutic value of digital interventions based on playful activities by assessing the release of hormones such as endorphins and striatal dopamine responsible for feelings of pleasure and well-being during the patient's interactive experiences with virtual reality [34,35].…”
Section: Virtual Realitymentioning
confidence: 99%
“…Virtual reality (VR) technology has been used widely in stroke rehabilitation for some years [5]. Previous studies demonstrated that VR was popular in the rehabilitation of upper extremity [6], lower extremity [7], cognition [8], psychology [9], et al Most of these studies employed commercial VR games or trained body function through intensive and repetitive practice. IADL assessment and training are full of challenges in real environments, and VR could be an alternative technology for overcoming these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, VR has been used in pain relief therapy as an attention distractor (Viderman et al, 2023). VR has also been shown to help relieve the symptoms of depression by constructing a relaxing and hopeful virtual world for patients (Liu et al, 2023). VR may also help patients adopt and use effective coping mechanisms by creating a safe and controlled environment that facilitates effective anxiety self-management (Donnelly et al, 2021).…”
mentioning
confidence: 99%